2019
DOI: 10.3389/fphar.2019.01361
|View full text |Cite
|
Sign up to set email alerts
|

Ma Xing Shi Gan Decoction Attenuates PM2.5 Induced Lung Injury via Inhibiting HMGB1/TLR4/NFκB Signal Pathway in Rat

Abstract: Ma Xing Shi Gan Decoction (MXD), a classical traditional Chinese medicine prescription, is widely used for the treatment of upper respiratory tract infection. However, the effect of MXD against particulate matters with diameter of less than 2.5 μm (PM2.5) induced lung injury remains to be elucidated. In this study, rats were stimulated with PM2.5 to induce lung injury. MXD was given orally once daily for five days. Lung tissues were harvested to assess pathological changes and edema. Myeloperoxidase (MPO) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 125 publications
1
24
0
Order By: Relevance
“…As one of the components of QFPD, Ma Xing Shi Gan Decoction has been vastly used in the treatment of multiple epidemics caused by viruses [45][46][47]. Previous studies showed that Ma Xing Shi Gan Decoction can alleviate viral infection by regulating the expression of multiple cytokines, activating multiple innate immune-related cells, and preventing pathogens from entering targeted host cells [48][49][50]. In this present study, LC-MS results suggested that the compatibility of Ma Xing Shi Gan Decoction increase the dissolution of ephedrine while reducing the dissolution of glycyrrhizic acid.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the components of QFPD, Ma Xing Shi Gan Decoction has been vastly used in the treatment of multiple epidemics caused by viruses [45][46][47]. Previous studies showed that Ma Xing Shi Gan Decoction can alleviate viral infection by regulating the expression of multiple cytokines, activating multiple innate immune-related cells, and preventing pathogens from entering targeted host cells [48][49][50]. In this present study, LC-MS results suggested that the compatibility of Ma Xing Shi Gan Decoction increase the dissolution of ephedrine while reducing the dissolution of glycyrrhizic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the anti-HMGB1 has no effect on the proliferation of the virus, in combination with peravimir a significant effect on neutrophil infiltration and macrophage aggregation was observed ( 57 ). Also Chloroquine ( 58 ), Methotrexate ( 59 ), anti-oxidants ( 60 62 ), traditional Chinese medicine ( 63 , 64 ), thrombomodulin ( 65 ), and others ( 66 68 ) are listed as potential therapeutic strategies to diminish HMGB1.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Optimal concentration selection of PM2.5 was evaluated with CCK8 kits (Solarbio, Beijing, China), and the concentration ranges of which were determined by referring to the published study [48]. Cells were stimulated with series concentrations of PM2.5 (5,10,15,20,25,30,35, and 40 μg/cm 2 ) for 48 h. en, 20 μL CCK8 solution was added, followed by an additional 2-hour incubation in an incubator at 37°C. e absorbance (450 nm) was determined with a microplate reader ( ermo scientific, USA, Multiskan FC).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…e optimal dose of PM2.5 and MXD for the present study was determined using the CCK8 kits. Primary alveolar cells were continuously exposed to PM2.5 at different concentrations (5,10,15,20,25,30,35, and 40 μg/cm 2 ) for 48 h. PM2.5 at the dose of 25 μg/cm 2 significantly decreased the cell viability by about 50%, which was chosen for the follow-up experiments ( Figure 5(a)).…”
Section: Determination Of the Optimal Concentration Of Pm25 And Mxd-mentioning
confidence: 99%